A graphene and hexagonal boron nitride reinforced titanium-based composite material and preparation method thereof
By introducing graphene and hexagonal boron nitride nanosheets into titanium-based composite materials, and using ball milling, rapid hot pressing sintering and hot rolling deformation methods, a specific interface structure is formed, which solves the problem of poor plasticity of titanium-based composite materials. , significantly improves its tensile properties and strong plasticity.
Patent Information
- Application Number
- CN202310141800.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-14
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-02-14
AI Technical Summary
While improving the tensile strength, existing titanium-based composite materials have poor plasticity and are difficult to meet the needs of high elongation.
By introducing graphene and hexagonal boron nitride nanosheets into the TC4 titanium alloy matrix, and using ball milling, rapid hot press sintering and hot rolling deformation, hexagonal boron nitride is formed by forming TiC-coated graphene and TiB whisker pinned hexagonal boron nitride by ball milling, rapid hot press sintering and hot rolling deformation methods. The interface structure improves the tensile performance of titanium-based composite materials.
The tensile properties and strong plasticity of graphene and hexagonal boron nitride are significantly improved, and the tensile properties and strong plasticity of titanium-based composite materials are met with high elongation.
Smart Images

Figure CN116162871B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a graphene and hexagonal boron nitride reinforced titanium-based composite material and a preparation method thereof, and in particular to a method for preparing the graphene and hexagonal boron nitride reinforced titanium-based composite material by utilizing spark plasma sintering or rapid hot pressing sintering and hot rolling deformation, and belongs to the technical field of metal-based composite material preparation. Background Art
[0002] Titanium alloy is an extremely important lightweight structural material with broad application prospects in the engineering field. After in-depth research in recent years, the performance of titanium materials has been rapidly improved, but it is still difficult to meet the material performance requirements of rapidly developing large-scale, multifunctional and complex components. Titanium-based composites (TMCs) have excellent impact resistance, high specific strength and low density, and are a structural material with great development prospects. Although a lot of research has been done on improving the mechanical properties of titanium-based composites, the type and content of the added reinforcement and the design of the interface structure between it and the titanium matrix are important prerequisites for achieving excellent mechanical properties of titanium-based composites.
[0003] For the preparation of TMCs, the tensile strength is generally improved by adding a high content (mass fraction greater than 10%) of reinforcement phase with a single interface structure into the titanium matrix, but the plasticity is often poor (elongation less than 5%), which limits its industrial application range. However, with the increasing requirements for lightweight applications, it is necessary to further improve the tensile strength of titanium alloys while maintaining good plasticity (>10%). Therefore, how to introduce a small amount of suitable type of reinforcement into the titanium matrix and regulate the interface reaction between it and the titanium matrix so that the prepared titanium-based composite material has excellent strength and plasticity is a problem that needs to be solved urgently in this field. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a graphene and hexagonal boron nitride reinforced titanium-based composite material and a preparation method thereof, wherein the matrix structure of the titanium-based composite material prepared by the method is an ultra-fine scale α p and β trans The interface structure between the reinforcement and the matrix is TiC-coated graphene and TiB whisker-pinned hexagonal boron nitride, which improves the tensile properties of the graphene and hexagonal boron nitride reinforced titanium-based composite material.
[0005] The technical solution of the present invention is:
[0006] A graphene and hexagonal boron nitride reinforced titanium-based composite material, the titanium-based composite material comprising a matrix and a reinforcement;
[0007] The matrix is TC4 titanium alloy, and the structure is ultra-fine α p and β trans ;
[0008] The reinforcement is graphene nanosheets and hexagonal boron nitride nanosheets;
[0009] The interface structure between the reinforcement and the matrix is TiC coated graphene and TiB whiskers pinned hexagonal boron nitride.
[0010] A method for preparing a graphene and hexagonal boron nitride reinforced titanium-based composite material, comprising the following steps:
[0011] (1) ball-milling the graphene nanosheets, hexagonal boron nitride nanosheets and TC4 titanium alloy powder in anhydrous ethanol to obtain a uniformly mixed slurry, and then removing the ball-milling medium and rotary drying to obtain a mixed powder;
[0012] Taking the sum of the mass of graphene nanosheets, hexagonal boron nitride nanosheets and TC4 titanium alloy powder as 100%, the mass fraction of graphene nanosheets is 0.05% to 0.25%, the mass fraction of hexagonal boron nitride nanosheets is 0.05% to 0.25%, and the mass fraction of TC4 titanium alloy powder is 99.90% to 99.50%;
[0013] Preferably, the average particle size of the TC4 titanium alloy powder is ≤55 μm;
[0014] Preferably, the thickness of a single graphene nanosheet is ≤100 nm, and the number of layers is >0 and ≤25; the thickness of a single hexagonal boron nitride sheet is ≤100 nm, and the number of layers is >0 and ≤25;
[0015] Preferably, the ball milling parameters are as follows: the ball milling medium is anhydrous ethanol, and when the mass of the powder is 30-50g, the volume of anhydrous ethanol used is 300-500mL; the rotation speed is 150r / min-300r / min, the time is 4h-12h, the ball-to-material ratio is (5-10):1, the grinding balls are composed of two sizes of agate balls, the two sizes of agate balls are large-sized agate balls and small-sized agate balls, the diameter of the large-sized agate balls is φ8-10mm, the diameter of the small-sized agate balls is 2-5mm, and the mass ratio of the large-sized agate balls to the small-sized agate balls is (3-10):1;
[0016] Preferably, the rotary evaporation drying process is as follows: after removing the grinding balls, the slurry is placed in an eggplant-shaped flask with a volume of 500 to 1000 mL, and vacuum dried at 65 to 80° C. for 0.5 to 1 h to completely evaporate the anhydrous ethanol, thereby obtaining a dry mixed powder;
[0017] (2) sintering, cooling, grinding, cleaning and drying the mixed powder by rapid hot pressing or spark plasma sintering to obtain a preformed body with a thickness of 5 to 10 mm;
[0018] Preferably, the sintering parameters are: vacuum degree <15Pa, heating rate of 100-200°C / min, sintering temperature of 500-600°C, sintering pressure of 300-900MPa, and holding time of 5-7min;
[0019] (3) hot rolling deformation treatment is performed on the preformed body by a twin-roll rolling mill to obtain a titanium-based composite material synergistically reinforced by TiC-coated graphene and TiB whisker-pinned hexagonal boron nitride. The specific operation steps of hot rolling deformation are as follows:
[0020] The preformed body obtained in step (2) is placed in a resistance furnace and kept at 850° C. to 950° C. for 5 to 10 minutes, and then immediately subjected to 5 to 7 passes of hot rolling with a deformation amount of 65% to 75%, and returned to the furnace for keeping warm for 3 to 6 minutes between passes. The hot-rolled sample is then placed in air to cool to room temperature, thereby obtaining a graphene and hexagonal boron nitride reinforced titanium-based composite material.
[0021] Beneficial Effects
[0022] (1) The present invention provides a method for preparing a graphene and hexagonal boron nitride reinforced titanium-based composite material, wherein the method uses graphene and hexagonal boron nitride nanosheets and TC4 titanium alloy powder as raw materials, and adopts ball milling, rapid hot pressing sintering and hot rolling treatment to obtain a TiC-coated graphene and TiB whisker-pinned hexagonal boron nitride reinforced titanium-based composite material. The matrix structure of the graphene and hexagonal boron nitride reinforced titanium-based composite material is an ultrafine-scale α p and β trans The interface structure between the reinforcement and the matrix is TiC coated graphene and TiB whiskers pinning hexagonal boron nitride, which improves the tensile properties of the graphene and hexagonal boron nitride reinforced titanium-based composite material. In the graphene and hexagonal boron nitride reinforced titanium-based composite material, the graphene is coated by two layers of TiC, the intrinsic structure of the middle graphene is well preserved; the intrinsic structure of the hexagonal boron nitride is well preserved, and the TiB whiskers pin it together with the titanium alloy matrix. The generation of these two interface structures strengthens the interface bonding strength between graphene and hexagonal boron nitride and the titanium alloy matrix.
[0023] (2) The present invention provides a method for preparing a titanium-based composite material reinforced with graphene and hexagonal boron nitride, which involves three stages. First, graphene and hexagonal boron nitride nanosheets are uniformly mixed with TC4 titanium alloy powder by ball milling, and then the mixed powder is sintered by rapid hot pressing sintering technology to prepare the powder into a block. This stage ensures the feasibility of subsequent hot rolling treatment. Finally, the sintered preformed body is hot rolled to refine the matrix structure, and the graphene and hexagonal boron nitride nanosheets are arranged in a directional manner along the rolling direction while reacting in situ with the titanium alloy matrix. In the titanium-based composite material, after the reaction of graphene and hexagonal boron nitride with the titanium alloy matrix, they respectively form a two-dimensional interface structure similar to a "sandwich" and a three-dimensional interface structure similar to a "cactus", and the addition of the two significantly refines the matrix structure, and strengthens the matrix according to the fine grain strengthening mechanism and the load transfer mechanism, thereby improving the strength of the titanium-based composite material. When the external stress is transmitted to the interfaces of the two different dimensions mentioned above, it will be distributed in multi-dimensional space, which can effectively alleviate local stress concentration and improve the stability of the interface structure.
[0024] (3) The present invention provides a method for preparing a graphene and hexagonal boron nitride reinforced titanium-based composite material. Compared with the traditional method of adding a single reinforcement, the present invention is the first to introduce graphene and hexagonal boron nitride nanosheets as reinforcements into a titanium alloy matrix through ball milling, rapid hot pressing sintering and hot rolling deformation. The operation is simple and easy, with low energy consumption, which is conducive to industrial application. The prepared titanium-based composite material has excellent strength-plasticity matching.
[0025] (4) The present invention relates to a method for preparing a titanium-based composite material reinforced with graphene and hexagonal boron nitride, and belongs to the technical field of preparation of metal-based composite materials. The titanium-based composite material is based on TC4 titanium alloy as a matrix, and graphene and hexagonal boron nitride nanosheets as a reinforcing phase. The preparation method is as follows: ball-milling the graphene, hexagonal boron nitride nanosheets and TC4 titanium alloy powder to obtain a uniform slurry, removing the ball milling medium and then rotary drying to obtain a mixed powder; sintering the mixed powder using a rapid hot pressing sintering system, and then hot rolling the sintered blank using a double-roll rolling mill to obtain a titanium-based composite material synergistically reinforced by TiC-coated graphene and TiB whisker-pinned hexagonal boron nitride. The matrix structure of the titanium-based composite material prepared by the method is an ultrafine-scale α p and β trans , which improves the tensile properties of the graphene and hexagonal boron nitride reinforced titanium-based composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is a SEM image of the mixed powder obtained in step (1) of the embodiment;
[0027] Figure 2is a SEM image of the mixed powder obtained in step (1) of the embodiment;
[0028] Figure 3 is a SEM image of the titanium-based composite material obtained in step (3) of the embodiment;
[0029] Figure 4 is a SEM image of the two-dimensional interface structure of TiC-coated graphene in the titanium-based composite material prepared in step (3) of the embodiment;
[0030] Figure 5 is a SEM image of the three-dimensional interface structure of TiB whiskers pinned hexagonal boron nitride in the titanium-based composite material prepared in step (3) of the embodiment;
[0031] Figure 6 This is a TEM image of the matrix structure of the titanium-based composite material obtained in step (3) of the embodiment. DETAILED DESCRIPTION
[0032] In order to make the objectives and technical solutions of the present invention clearer, the technical solutions of the present invention will be fully described below in conjunction with specific examples. It should be noted that this example is only a part of the embodiments of the present invention. Based on the embodiments of the present invention, other examples obtained by those skilled in the art without creative work are all within the protection scope of the present invention.
[0033] A method for preparing a graphene and hexagonal boron nitride reinforced titanium-based composite material, the specific steps are as follows:
[0034] (1) Graphene, hexagonal boron nitride nanosheets and TC4 titanium alloy powder are ball-milled in anhydrous ethanol to obtain a uniformly mixed slurry, and the ball-milling medium is removed and then rotary dried to obtain a mixed powder.
[0035] (2) Sintering, cooling, grinding, cleaning and drying the mixed powder by rapid hot pressing or spark plasma sintering to obtain a preformed body with a thickness of 5 to 10 mm.
[0036] (3) The preformed body is subjected to hot rolling deformation treatment using a twin-roll rolling mill to obtain a titanium-based composite material synergistically reinforced by TiC-coated graphene and TiB whisker-pinned hexagonal boron nitride.
[0037] The mass fraction of the graphene and hexagonal boron nitride nanosheets is 0.10% to 0.45%, the mass fraction of the TC4 titanium alloy is 99.90% to 99.55%, and the average particle size of the TC4 titanium alloy powder is ≤55 μm; the thickness of a single graphene nanosheet is ≤100 nm, and the number of layers is greater than 0 and ≤25; the thickness of a single hexagonal boron nitride sheet is ≤100 nm, and the number of layers is greater than 0 and ≤25; the content of anhydrous ethanol is 300 to 500 ML; the rotation speed is 150 r / m in~300r / min, time 4h~12h, ball-to-material ratio (5~10):1, the mass ratio of the grinding balls is (3~10):1, the agate balls with a diameter of φ8~10mm and a diameter of φ2~5mm; the rotary evaporation drying process is: after removing the grinding balls, the slurry is placed in an eggplant-shaped flask with a volume of 500~1000ML, and vacuum dried at 65~80℃ for 0.5~1h to completely evaporate the anhydrous ethanol, so as to obtain a dry mixed powder.
[0038] The sintering parameters are: vacuum degree <15Pa, heating rate of 100-200°C / min, sintering temperature of 500-600°C, sintering pressure of 300-900MPa, and holding time of 5-7min.
[0039] The thickness of the sample is 5-10 mm, the rolling temperature is 850°C-950°C, the rolling deformation is 65-75%, the first pass holding time is 5-10 min, the re-melting holding time between passes is 3-6 min, and 5-7 passes are required to complete the process.
[0040] In the following embodiments:
[0041] The TC4 powder was purchased from Keyuan New Metal Materials Trading Company in Zhanggong District, Ganzhou City, and the average particle size was 33 μm.
[0042] The graphene and boron nitride nanosheets were purchased from Xianfeng Nanomaterial Co., Ltd., with purities of 97.8% and 98.1% respectively, with 5 to 25 layers and 5 to 30 layers respectively, and thicknesses of 8 to 20 nm and 5 to 30 nm respectively.
[0043] The model of the rapid hot pressing sintering system is FHP-858, which was purchased from Suzhou Hateng Technology Co., Ltd.
[0044] The twin-roller mill model is LG-02, purchased from Zhengzhou Hengzhong Heavy Industry Machinery Manufacturing Co., Ltd.
[0045] The titanium-based composite materials prepared in each embodiment were tested as follows:
[0046] (1) Tensile test equipment: A Zwick Z2.5 TH single-column tabletop electronic universal testing machine (manufactured by the ZwickRoell Group of Germany and equipped with a laser X tens laser extensometer) was used.
[0047] (2) SEM test: The scanning electron microscope (SEM) was used with a JEOL JSM 7200F instrument.
[0048] (3) TEM test: The instrument model of transmission electron microscope (TEM) is TEM, FEI Tecnai G2 F20.
[0049] Example
[0050] (1) Weigh 45 g of TC4 titanium alloy powder with an average particle size of 33 μm, 0.09 g of graphene and 0.04 g of hexagonal boron nitride nanosheets and mix them in a ball mill, wherein the ball milling medium is 400 ml of anhydrous ethanol, the ball-to-material ratio is 8:1, the ball mill speed is 200 r / min, and the ball milling time is 6 h; after the ball milling slurry is removed from the grinding balls, it is placed in a 1000 ml eggplant-shaped flask for vacuum rotary evaporation treatment, wherein the temperature of the water bath is 70 ° C, and the composite powder is obtained after rotary evaporation drying.
[0051] (2) 12 g of the composite powder was placed in a cemented carbide mold with a diameter of 25 mm, and the composite powder was sintered into a block by a rapid hot pressing sintering system. The specific sintering parameters were: heating rate 100°C / s, sintering temperature 550°C, holding time 5 min, sintering pressure 750 MPa, and cooling rate 100°C / s. After sintering, the powder was taken out and air-cooled to room temperature.
[0052] (3) The block obtained in step (2) is polished and cleaned to remove surface defects, kept in a preheated 850°C resistance furnace for 10 minutes, and immediately taken out for rolling treatment, with 7 passes of rolling with a deformation of 75%, and returned to the furnace for 5 minutes between passes. After the last pass of rolling, it is air-cooled to room temperature. This is a graphene and hexagonal boron nitride reinforced titanium-based composite material.
[0053] The composite powder in this embodiment and the prepared graphene and hexagonal boron nitride reinforced titanium-based composite material were tested accordingly, and the results are as follows:
[0054] (1) The graphene, hexagonal boron nitride nanosheets and TC4 titanium alloy composite powder were observed using a field emission scanning electron microscope. The test results are shown in Figure 1 and Figure 2 , the TC4 titanium alloy sphere did not undergo obvious deformation and breakage, and the graphene and boron nitride nanosheets were evenly distributed on the TC4 titanium alloy sphere.
[0055] (2) The microstructure of the graphene and hexagonal boron nitride reinforced titanium-based composite material was observed using a field emission scanning electron microscope. The test results are shown in Figure 3-Figure 5No obvious holes were found in the matrix, the density of the plate was good, the graphene and boron nitride nanosheets were oriented along the rolling direction, and both had appropriate interface reactions with the titanium alloy matrix, which greatly improved the interface bonding strength with the titanium alloy matrix, and could effectively exert the strengthening and toughening effects of both.
[0056] (3) The microstructure of the graphene and hexagonal boron nitride reinforced titanium-based composite material matrix was observed using a transmission electron microscope. The test results are shown in Figure 6 , the matrix is mainly composed of ultra-fine α p and β trans , β trans The appearance of increases the total interface density between the phases in the matrix structure, which can effectively improve the strength of the composite material.
[0057] (4) Room temperature tensile test: The room temperature tensile strength of the graphene and hexagonal boron nitride reinforced titanium-based composite material is 1300.86 MPa, the yield strength is 1017.62 MPa, and the elongation is 11.54%.
[0058] The above embodiments are only used to illustrate the present invention and do not limit the technical solutions in the present invention. Those skilled in the art may modify or replace the present invention to a certain extent, and any modification that does not deviate from the spirit of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A graphene and hexagonal boron nitride reinforced titanium-based composite material, characterized in that: (1) Weighing 45 g of TC4 titanium alloy powder with an average particle size of 33 μm, 0.09 g of graphene and 0.04 g of hexagonal boron nitride nanosheets, and mixing them in a ball mill, wherein the ball milling medium is 400 ml of anhydrous ethanol, the ball-to-material ratio is 8:1, the ball mill speed is 200 r / min, and the ball milling time is 6 h; after removing the grinding balls from the ball-milled slurry, place it in a 1000 ml eggplant-shaped flask for vacuum rotary evaporation treatment, wherein the temperature of the water bath is 70° C., and after rotary evaporation drying, a composite powder is obtained; (2) 12 g of the composite powder was placed in a cemented carbide mold with a diameter of 25 mm, and the composite powder was sintered into a block by a rapid hot pressing sintering system. The specific sintering parameters were: heating rate 100 °C / s, sintering temperature 550 °C, holding time 5 min, sintering pressure 750 MPa, cooling rate 100 °C / s, and after sintering, the powder was taken out and air-cooled to room temperature; (3) grinding and cleaning the block obtained in step (2) to remove surface defects, keeping it in a resistance furnace that has been preheated to 850° C. for 10 minutes, and immediately taking it out for rolling treatment, with 7 rolling passes with a deformation of 75%, returning to the furnace for 5 minutes between passes, and air cooling to room temperature after the last rolling pass to obtain a graphene and hexagonal boron nitride reinforced titanium-based composite material; The prepared graphene and hexagonal boron nitride reinforced titanium-based composite materials were tested, and the results are as follows: The TC4 titanium alloy sphere did not undergo obvious deformation and breakage, and graphene and boron nitride nanosheets were evenly distributed on the TC4 titanium alloy sphere; Graphene and boron nitride nanosheets were oriented along the rolling direction and both had appropriate interfacial reactions with the titanium alloy matrix; The room temperature tensile strength is 1300.86MPa, the yield strength is 1017.62MPa, and the elongation is 11.54%.
Citation Information
Patent Citations
Nickel-based self-lubricating composite material with wide temperature range and preparation method thereof
CN108330332A
Preparing method capable of achieving TC4 titanium alloy high toughness through co-reinforcement method
CN111644615A